A competitive algorithm for throughput maximization on identical machines - Moseley, Benjamin; Pruhs, Kirk; Stein, Clifford; Zhou, Rudy (Mathematical programming, 2024)
This paper considers the basic problem of scheduling jobs online with preemption to maximize the number of jobs completed by their deadline on m identical machines. The main result is an O (1) competitive deterministic algorithm for any number of machines m > 1 .